Efficacy and safety of sacubitril/valsartan on heart failure with preserved ejection fraction: A meta-analysis of randomized controlled trials - Yu, Wanqian; Zhang, Hongzhou; Shen, Wen; Luo, Fan; Yang, Shuai; Gan, Lujin; Zhao, Yuanbin; Yang, Pingping; Wu, Qinghua (Frontiers in Cardiovascular Medicine, 2022)
Aims: The efficacy and safety of sacubitril/valsartan for patients with heart failure with preserved ejection fraction (HFpEF) are controversial. Hence, the primary objective of the study was to evaluate the efficacy and safety of sacubitril/valsartan treatment for patients with HFpEF. Methods and results: We searched for randomized controlled trials of sacubitril‐valsartan in patients with HFpEF in the PubMed, Embase, and Web of Science databases. Three studies that involved a total of 7663 patients were eligible for inclusion. Sacubitril‐valsartan reduced the risk of hospitalization for HF (OR: 0.78; 95% CI: 0.70–0.88; P < 0.0001) and the incidence of worsening renal function (RR: 0.79, p = 0.002) among HFpEF patients in the three trials, but there was no significant reduction in all-cause mortality (0.99, 95% CI 0.84–1.15; P =0.86) or cardiovascular mortality (0.95, 95% CI 0.78–1.15; P =0.16). Moreover, sacubitril/valsartan was associated with an increased the risk of symptomatic hypotension (RR: 1.44; p <0.00001) and angioedema (RR: 2.66; p < 0.04), there was no superiority for decreasing the incidence of hyperkalaemia (RR: 0.89; p = 0.11). Conclusion: Compared with valsartan or individualized medical therapy (IMT), sacubitril/valsartan significantly decreased the risk of hospitalization for HF and reduced the incidence of renal dysfunction.